2017
DOI: 10.1111/cas.13453
|View full text |Cite
|
Sign up to set email alerts
|

HOXC13 promotes proliferation of esophageal squamous cell carcinoma via repressing transcription ofCASP3

Abstract: Esophageal squamous cell carcinoma (ESCC), the dominant subtype of esophageal cancer, is one of the most common digestive tumors worldwide. In this study, we confirmed that HOXC13, a member of the homeobox HOXC gene family, was significantly upregulated in ESCC and its overexpression was associated with poorer clinical characteristics and worse prognosis. Moreover, knockdown of HOXC13 inhibited proliferation and induced apoptosis of ESCC through upregulating CASP3. ChIP analysis revealed that HOXC13 repressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…These differences may be related to the ethnicity of the individuals studied, their lifestyle, diet or other lifestyle factors. Upregulation of HOXC13 has been reported in odontogenic tumors, liposarcoma, metastatic melanoma, esophageal squamous cell carcinoma, lung adenocarcinoma and ameloblastoma (32)(33)(34)(35)(36)(37). However, the expression levels of HOXC13 in CRC was not significantly altered in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be related to the ethnicity of the individuals studied, their lifestyle, diet or other lifestyle factors. Upregulation of HOXC13 has been reported in odontogenic tumors, liposarcoma, metastatic melanoma, esophageal squamous cell carcinoma, lung adenocarcinoma and ameloblastoma (32)(33)(34)(35)(36)(37). However, the expression levels of HOXC13 in CRC was not significantly altered in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…HOXC13 is overexpressed in metastatic melanoma tissues compared to primary melanoma tissues and is targeted by miR‐503 in esophageal squamous cell carcinoma. It has been shown that HOXC13 promotes proliferation and inhibits apoptosis of ESCC …”
Section: Discussionmentioning
confidence: 99%
“…34 Increasing evidence suggests that HOXC13 regulates cell proliferation in several tumors such as lung adenocarcinoma, esophageal squamous cell carcinoma and nasopharyngeal carcinoma. [35][36][37] However, it remains unclear whether HOXC13 regulates the proliferation of AB cells. In the present study, HOXC13 was up-regulated in 26 AB tissues.…”
Section: Discussionmentioning
confidence: 99%